PhyloTree Build 17: Growing the human mitochondrial DNA tree. (December 2015) - van Oven, Mannis
Abstract: An accurate, up-to-date, detailed and global phylogenetic tree of human mitochondrial DNA (mtDNA) is essential for various forensic mtDNA applications including data quality control and haplogroup assignment for biogeographic ancestry inference. PhyloTree (http://www.phylotree.org ) is widely accepted as the reference phylogeny for human mtDNA. Here, a new update of PhyloTree, Build 17, is introduced, comprising nearly 5.5 thousand haplogroups.